The Assemblies of God: godly love and the revitalization of American Pentecostalism - Poloma, Margaret M. (New York University Press, 2010)
The Assemblies of God draws on fresh, up-to-date research including quantitative surveys and interviews conducted within twenty-two Assemblies of God congregations to offer a new sociological portrait of the AG for the new millennium. The authors suggest that there is a revitalization of the movement in the works within the context of the larger Pentecostal upswing, and that this revitalization may be spurred by what the authors call "godly love" : the dynamic interaction between perceived divine and human love that enlivens and expands adherents' benevolence